Ground Penetrating Radar Investigation of a Mass Grave and Malina Entrance at the HKP Site, Vilnius, Lithuania - Jol, Harry M.; Mataitis, Richard J.; Beck, Joseph D.; Burds, Luke T. (My University, 2018)
Major Karl Plague was a German officer during World War Two responsible for saving 250 Jewish forced labor workers at HKP 562 in Vilnius, Lithuania. The 750 other workers were captured and killed by Nazi SS members on their retreat out of the country during Adolf Hitler’s “Final Solution", their bodies buried in an unmarked grave. In the summer of 2017, an international team of Jewish scholars, archaeologists and geophysicists were invited to HKP to investigate two possible locations in which the mass grave may exist using ground penetrating radar (GPR). GPR is a noninvasive technology that sends electromagnetic frequencies into the subsurface to examine its stratigraphy. Using 225 and 450 MHz antennae with a step size of 0.1m and 0.05m (respectively), GPR data was collected over 6 grids, varying in size. Grids were located over a monument to those slaughtered, along the back wall of one of the buildings, and in the basement of the same building. GPR data was then processed using EKKO_Project and Voxler to examine the subsurface. Results showed extensive stratigraphic dipping along the back side of the building along with an anomaly in the basement believed to be the entrance to a malina.
Color poster with text, images, and maps.
Keywords: Posters; Lithuania; Vilnius, Lithuania; Ground penetrating radar; Plague, Karl; World War, 1939-1945; Holocaust, Jewish (1939-1945)--Lithuania